Palestinian Teachers' Views on the Factors That Limit Students' Creativity and Some Possible Strategies to Overcome Them - Ahmed Awad Raba'; Hussam Tawfeeq Harzallah (Research in Social Sciences and Technology, 2018)
This study seeks to investigate the degree of enhancing creative thinking skills in the English for Palestine and math curricula from the teachers of English and math perspectives. To accomplish this aim, the researchers used a 20-item questionnaire and a 5-question interview. Findings of the research showed that the degree of using creative thinking in schools and curricula is low and inadequate. In the light of these findings, the researchers recommended divergent methods of teaching, adequate training for teachers and students on different techniques and the inclusion of activities in the curricula to improve students’ creative thinking.